2011
DOI: 10.1016/j.virol.2011.01.029
|View full text |Cite
|
Sign up to set email alerts
|

The ability of pandemic influenza virus hemagglutinins to induce lower respiratory pathology is associated with decreased surfactant protein D binding

Abstract: Pandemic influenza viral infections have been associated with viral pneumonia. Chimeric influenza viruses with the hemagglutinin segment of the 1918, 1957, 1968 or 2009 pandemic influenza viruses in the context of a seasonal H1N1 influenza genome were constructed to analyze the role of hemagglutinin (HA) in pathogenesis and cell tropism in a mouse model. We also explored whether there was an association between the ability of lung surfactant protein D (SP-D) to bind to the HA and the ability of the correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
83
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 55 publications
3
83
1
Order By: Relevance
“…We also show that D325AϩR343V can inhibit infectivity of a viral strain containing the HA of the 1918 H1N1. Previous studies showed that wild-type, native SP-D does not inhibit this strain in vitro or in vivo (21). The 1918 HA has high homology with the 2009 HA (including having the same glycan attachment sites) (23).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…We also show that D325AϩR343V can inhibit infectivity of a viral strain containing the HA of the 1918 H1N1. Previous studies showed that wild-type, native SP-D does not inhibit this strain in vitro or in vivo (21). The 1918 HA has high homology with the 2009 HA (including having the same glycan attachment sites) (23).…”
Section: Discussionmentioning
confidence: 91%
“…After thawing, the viral stocks contained ϳ5 ϫ 10 8 infectious focusforming units/ml. The California 2009 H1N1 pandemic strain (Cal09) and the New York 2001 H1N1 (NY01) seasonal strains were prepared by reverse genetics as described (21,27). Additional strains related to the 2009 pandemic strain were developed by reverse genetics, including a strain containing only the HA gene of the pandemic Mexico 2009 H1N1 combined with the other seven genes of NY01 (Mex 1:7) and an additional strain containing the HA and neuraminidase (NA) of Mexico 2009 (Mex 2:6).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The extents of glycosylation and the HA patterns determine the sensitivity of viruses to lectin-mediated innate defenses. In addition, pandemic pH1N1 and avian H5N1 and H7N9 viruses were resistant to soluble C-type lectin surfactant protein D in host cells, and this resulted in decreased antiviral activities in mice and significant pathology in the mouse lower respiratory tract (33,34). Another report indicated that the macrophage MR recognized the same spectrum of monosaccharides as the collectins do and served as a major endocytic receptor in the infectious entry of influenza virus into murine macrophages (35).…”
Section: Discussionmentioning
confidence: 99%